Absolute quantification of viral proteins from pseudotyped VSV-GP using UPLC-MRM - Basu, Rajeswari; Dambra, Richard; Jiang, Di; Schätzlein, Sophia A.; Njiyang, Shu; Ashour, Joseph; Chiramel, Abhilash I.; Vigil, Adam; Papov, Vladimir V. (Microbiology spectrum, 2024)
The development of oncolytic viral therapy has gained considerable momentum in recent years. Vesicular stomatitis virus glycoprotein (VSV-GP) is a new biotherapeutic emerging in the oncolytic viral therapy platform. Novel analytical assays that can accurately and precisely quantify the viral proteins are a necessity for the successful development of viral vector as a biotherapeutic. We developed an ultra-high performance liquid chromatography multiple reaction monitoring-based assay to quantify the absolute concentrations of the different structural proteins of VSV-GP. The complete processing of GP complex (GPC) is a prerequisite for the infectivity of the virus. The assay extends the potential for quantifying full-length GPC, which provides an understanding of the processing of GPC (along with the quantification of GP1 and GP2 separately). We used this assay in tracking GPC processing in HEK-293-F production cell lines infected with VSV-GP.